Impact of fire exclusion and aspect on soil carbon fractions in Afromontane grasslands, Cathedral Peak, South Africa. - (:unkn) unknown (My University, 2024)
Despite the importance of South Africa's Afromontane grasslands for ecosystem services (water supply and biodiversity), soil organic carbon (SOC) research remains limited. These grasslands evolved with fire, and fire exclusion leads to native plant afforestation. This study investigated SOC fractions and origin to understand the impact of fire-exclusion-driven afforestation and aspect on SOC storage in Afromontane grasslands. This study in Cathedral Peak Research Catchments, initiated in the 1940s, compared an afforested fire-excluded site (AF) to a periodically burnt (accidental fires, 2–5 years interval) grassland (PB) within the same catchment (Catchment-IX). Additionally, it compared a south-facing periodically burnt grassland (Catchment-IX) to a north-facing biennially burnt grassland (Catchment-VI). Soil samples collected at soil-depth increments (0–5, 5–10, 10–15, 15–20, 20–30, 30–60 and 60–100 cm) revealed that, within Catchment IX, PB had more topsoil SOC stocks and microbial activity than AF but similar active carbon (C) concentrations. As expected, δ13C values revealed that SOC in PB originates from C4 grasses, whilst it mostly originates from C3 plants in AF. The south-facing slope (Catchment-IX) had more SOC stocks, microbial activity and active C compared to the north-facing slope (Catchment-VI). Fire-exclusion-driven afforestation changed SOC input from roots to litter, thus reducing SOC storage. Cooler south-facing slopes are better C reservoirs. Afromontane grasslands show greater potential for C sequestration than afforested systems.
Keywords: African Research